Numerical Study of Chord Length and Twist angle Effect towards NACA 4415-FX60 Airfoil Combination in Horizontal Wind Turbines Application - Hangga Wicaksono; Kris Witono; Akhmad Faizin; Budi Eko Prasetyo (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2024)
The selection of the appropriate blade shape requires optimization in order to be applied to the relatively low wind conditions in Indonesia. This study proposed a new approach of wind turbine blades design by utilizing the combination of NACA 4415 and FX 60. The effect of twist angle and the chord length carried out in this study to better understanding the blades characteristics. The 6 DoF analysis can be used to determines the theoretical mechanical power of the wind turbine blades. The blade twist geometry analyzed in this study is 15, 20, and 25 degree. From the simulation results, the highest mechanical power was obtained on blades with a twist angle of 5 degrees and a chord length of 0.15m with an average value of 39.95 W. The simulation results show that, at a speed of 8 m/s the blade with a chord length of 0.2 m and a twist angle of 5o has the greatest torque of 5.16579 Nm, with a rotational speed of 76.0668 rpm per minute, this combination can be applied to a low rpm generator A twist angle can improve torque distribution along the blade, but a twist angle that is too sharp can reduce lift and increase drag. It was found that a wider chord length tends to produce lower rotation in the wind turbine. This is caused by the increased surface area on the turbine blade with a longer chord length, which results in an increase in the torque required to rotate the blade at a given speed.